Imaging particles in solid/air flows using an optical tomography system based on complementary metal oxide semiconductor area image sensors - Idroas, Mariani (Elsevier, 2015)
Particle characterization has become important in the pharmaceutical, food, paint and chemical industries, among others. For example, particle size and shape can affect the taste, texture, and appearance of food. Particle characterization has become more significant for on-line production control because it influences product quality. Moreover, the images of particles generated from on-line measurements can better characterize the process itself. This paper discusses the development of an optical tomography system based on a complementary metal oxide semiconductor (CMOS) area image sensor, which is used for imaging particles in solid/air flows. The system consists of a lighting system, a measurement system and a data acquisition system. The CMOS area image sensor has a pixel size of 5.2 µm × 5.2 µm, which provides a resolution of 1280 × 1024 pixels. A two-projection system is adopted to enable image reconstruction; in this system, two CMOS area image sensors are configured around a pipe, and a light source is placed on the opposite side of the pipe. When the light illuminates through the pipe, the shadows of any particles in the pipe will be cast onto the CMOS area image sensors. Four experiments on solid particles in air under different conditions are performed. The output of the CMOS area image sensor is processed to reconstruct the tomographic image. The results indicate that CMOS based optical tomography is capable of imaging particles in solid/air flows